(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this report, a technological project is proposed for an ecological greenhouse designed for the cultivation of leafy vegetables, root fruits, spices and aquaculture based on aquaponics. The cycle of sowing, growing, picking the finished product, packaging and shipping is isolated from the external environment and the technology implies optimization of energy resources, seed material, production costs, etc. This ecosystem is innovating the vertical farming industry with high-tech control systems to produce quality and clean produce, reducing costs and making it an attractive option for farmers today.